2022
DOI: 10.3390/su142214771
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Sustainability-Oriented Innovation in the Social Enterprises

Abstract: Sustainability-oriented innovation (SOI) is a subset of innovation that focuses on not just maximizing profits but also on minimizing negative consequences for the environment and society. Despite the fact that the study of SOI has grown rapidly in recent years, little is known about how SOI takes place in social enterprises (SEs). The aim of this study is to understand SOI in SEs with two research questions focusing on the current state of the research and the identification of emergent themes and subthemes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…To finish the preceding debate on the importance of eco-innovation in deciding on the application of the concept of sustainable economic growth, it is obvious that eco-innovation is vital for attaining sustainable growth in light of the globalization of economies and its effect on global pollution and the use of scarce resources. Thus, eco-innovation arises as a chance to develop sustainable technologies for production sustainability, green energy, eco-efficiency, and consumption awareness [8][9][10]15,22]. Roleders et al [44] evaluated the main components of eco-innovation activities in achieving sustainable development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To finish the preceding debate on the importance of eco-innovation in deciding on the application of the concept of sustainable economic growth, it is obvious that eco-innovation is vital for attaining sustainable growth in light of the globalization of economies and its effect on global pollution and the use of scarce resources. Thus, eco-innovation arises as a chance to develop sustainable technologies for production sustainability, green energy, eco-efficiency, and consumption awareness [8][9][10]15,22]. Roleders et al [44] evaluated the main components of eco-innovation activities in achieving sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…Industry must not only reframe its social and economic duties regarding the environment, but also invest in eco-innovation activities that maximize economic gain while minimizing environmental harm [6]. In the literature, eco-innovation [7] was formulated in various ways, such as Green Innovation [8,9], Sustainable Innovation [10,11], Ecologic Innovation [12,13], and Environmental Innovation [14,15]; however, the concept of eco-innovation has been used significantly in recent years [16]. The term "eco-innovation" refers to the development of novel and economically viable goods, processes, systems, services, and design processes that satisfy human needs while reducing the consumption of natural resources and the emission of hazardous chemicals through their existence [17].…”
Section: Eco-innovation and Eco-efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…First, ICT plays a role in driving economic growth and can also directly increase productivity, while the second role is that ICT can lead to firm innovation which can also increase the total factor productivity (TFP) of the economy (Díaz‐Chao et al, 2015). ICT‐based innovations and applications have become major drivers of enhanced organizational performance, economic growth, and social change (Harsanto, Mulyana, Faisal, & Shandy, 2022; Harsanto, Mulyana, Faisal, Shandy, & Alam, 2022; Yunis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Aouadi and Marsat [1] also suggested that the management of companies that integrate ESG strategies are better able to secure competitive advantage, improve operational efficiency, maintain reputation, reduce waste, and ultimately enhance shared value and sustainability with stakeholders. A study by Harsanto et al [2] has reviewed the literature on sustainability-oriented innovation in social enterprises, which found that process and organizational innovation, such as business model transformation and stakeholder management, can help social enterprises to increase their social impact. Mercedes Rubio-Andrés and Abril [3] discussed that sustainability-oriented innovation is closely related to organizational values.…”
Section: Introduction 1the Background and Needs Of The Studymentioning
confidence: 99%